2021
DOI: 10.1016/j.eclinm.2021.101113
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, acceptance and hesitancy among the general population worldwide to receive the COVID-19 vaccines and their contributing factors: A systematic review

Abstract: Background High rates of vaccination worldwide are required to establish a herd immunity and stop the current COVID-19 pandemic evolution. Vaccine hesitancy is a major barrier in achieving herd immunity across different populations. This study sought to conduct a systematic review of the current literature regarding attitudes and hesitancy to receiving COVID-19 vaccination worldwide. Methods A systematic literature search of PubMed and Web of Science was performed on Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
318
6
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(367 citation statements)
references
References 245 publications
(150 reference statements)
30
318
6
13
Order By: Relevance
“…It reported that being male, being elderly, having a higher income, having a higher education level, being a physician (compared with other healthcare professions), having private insurance and having prior vaccination history were important predictors of COVID-19 vaccination acceptance. 53 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It reported that being male, being elderly, having a higher income, having a higher education level, being a physician (compared with other healthcare professions), having private insurance and having prior vaccination history were important predictors of COVID-19 vaccination acceptance. 53 …”
Section: Discussionmentioning
confidence: 99%
“…It reported that being male, being elderly, having a higher income, having a higher education level, being a physician (compared with other healthcare professions), having private insurance and having prior vaccination history were important predictors of COVID-19 vaccination acceptance. 53 It has have been documented that pregnant women have no increase incidence of COVID-19 infection in comparison to the general population. However, it has been documented that pregnant women who contract the virus may have more severe forms of COVID-19 diseases.…”
mentioning
confidence: 99%
“…This study was based on the anonymous, self-designed, and structured online questionnaire (Supplementary Materials) that was made available through a media release by the Polish Press Agency (the single largest source of news in Poland) and Wirtualna Polska (the most viewed online source of news in Poland), subsequently shared by a number of other media outlets and their associated social media profiles, leading to the snowball effect. Such online research is preferable to swiftly reaching a group of individuals during the pandemic [32] and has been successfully employed in previous investigations on vaccine hesitancy [33,34].…”
Section: Surveymentioning
confidence: 99%
“…Until now, several questionnaires and scales have created to examine psychological impact of COVID-19 and mainly examine stress, anxiety or fear (Ahorsu et al, 2020;Arpaci et al, 2020;Feng et al, 2020;Lee, 2020;Lins and Aquino, 2020;Repišti et al, 2020;Taylor et al, 2020;Voitsidis et al, 2021). Also, several other questionnaires have developed to measure knowledge, attitudes, and practices about the COVID-19 (Bekele et al, 2020;Dardas et al, 2020;Patelarou et al, 2020;Saadatjoo et al, 2021;Srichan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From early 2021, the ability to vaccinate against the COVID-19 with safe and effective vaccines is the best hope to control the pandemic (Baden et al, 2021; Haas et al, 2021; Polack et al, 2020). Unfortunately the intention to vaccinate against the COVID-19 is low not only in the general population but also among healthcare professionals with some countries showing higher hesitancy rates compared with others (Cascini et al, 2021; Galanis et al, 2020; Galanis, Vraka, Siskou, et al, 2021a, 2021b; Luo et al, 2021; Salomoni et al, 2021; Snehota et al, 2021). Moreover, several factors influence the intention to vaccinate against the COVID-19 such as socio-demographic characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%